AUDIT QUALITY: THE INTERPLAY OF AUDITOR COMPETENCE, PROFESSIONALISM, AND TIME PRESSURE IN PUBLIC ACCOUNTING FIRMS - Rival Andiga Juanda; Maya Sari; Dahrani Dahrani (RADJA PUBLIKA, 2025)
This study examines and analyses the effect of auditor competence and professionalism on audit quality with time pressure as a moderating variable in Public Accounting Firms in Medan. This study uses a quantitative approach with primary data obtained through the distribution of questionnaires to auditors as respondents. The population in this study consisted of all auditors working at 23 Public Accounting Firms in Medan who were still actively registered, with a total of 69 auditors. The sampling technique was saturated, so all population members were included in the research sample. The analysis method used was descriptive and verificative, with the help of the SmartPLS version 4.0 application through the Structural Equation Modelling Partial Least Squares (SEM-PLS) approach, which is considered appropriate for comprehensively testing the relationship between variables. The study's results indicate that auditor competence has a positive and significant effect on audit quality, so the higher the auditor's competence, the better the audit quality. In addition, auditor professionalism also has a positive effect on audit quality, which confirms the importance of integrity, independence, and compliance with professional standards. Furthermore, time pressure was not found to moderate the relationship between auditor competence and audit quality, meaning competent auditors can still maintain quality even under time constraints. However, time pressure was found to moderate the relationship between auditor professionalism and audit quality, where high pressure tends to weaken the application of auditor professionalism.